Determinants of pattern in fynbos vegetation: physical site factors, disturbance regime, species attributes and temporal change - Privett, Sean David John (Department of Biological Sciences, 2016)
This study set out to explore the patterns and determinants of contemporary species distribution in a fynbos landscape based on information on 1) physical habitat characteristics, 2) past disturbance regime, 3) intrinsic properties of individual species and 4) temporal change in communities. The body of the thesis is divided into four parts covering each of these aspects individually. Each chapter has been written up as an individual paper and thus includes some repetition as well as cross-referencing. Each chapter includes a detailed rationale for the study in the introduction, as well as methods, results and a discussion of the findings. Chapter 2 describes the patterns of vegetation units in the Cape of Good Hope Nature Reserve and provides a quantitative assessment of the importance of physical site features as determinants of these units. These results are compared with the vegetation classifications of the area derived in earlier studies by Taylor (1984b) and Cowling et al. (1996a). Chapter 3 is the first study in fynbos to partition the variance in vegetation pattern into that explained by physical site factors and that explained by the recent disturbance regime. The study explores the role of 30 years of fire and alien plant infestations in influencing species distribution at the community and landscape scale. While a number of studies have explored spatial determinants of diversity and pattern in fynbos, temporal change within communities has been neglected. High levels of species turnover through time, as a result of colonisation and extinction, could be an important component of diversity at the landscape scale. Hence Chapters 4 and 5 both explore aspects of temporal dynamics in fynbos. The objectives of Chapter 4 are to determine the stability of populations at the landscape scale over a 30-year period and to establish the determinants of local extinction of species. Information on the stability of species over time and the attributes which enable species to persist or go extinct are important for understanding potential impacts of management practices as well as the importance of temporal dynamics in influencing spatial patterns. This is especially appropriate in the context of the results of Chapter 3, which suggest that a high proportion of the variance in species composition is unexplained despite the inclusion of physical factors, and past disturbance regime. The fifth chapter provides a descriptive account of the change in vegetation composition over a 30-year period. It is recommended that those readers not familiar with the fynbos system read it as it provides an overview of a variety of aspects of fynbos dynamics. Its objective is to show how the various components of the disturbance regime, as well as fluctuations in abundance of overstorey Proteaceae and their resultant competitive effects can influence community composition. The final chapter is a general discussion that summarises the major findings of the study.